Sophisticated attacks on decoy ballots: A devil's menu and the market for lemons - Hans Gersbach; Oriol Tejada; Akaki Mamageishvili (ETH Zurich, CER-ETH - Center of Economic Research, 2017)
Decoy ballots do not count in election outcomes, but otherwise they are indistinguishable from real ballots. By means of a game-theoretical model, we show that decoy ballots may not provide effective protection against a malevolent adversary trying to buy real ballots. If the citizenry is divided into subgroups (or districts), the adversary can construct a so-called "Devil's Menu" consisting of several prices. In equilibrium, the adversary can buy the real ballots of any strict subset of districts at a price corresponding to the willingness to sell on the part of the citizens holding such ballots. By contrast, decoy voters are trapped into selling their ballots at a low, or even negligible, price. Blowing up the adversary's budget by introducing decoy ballots may thus turn out to be futile. The Devil's Menu can also be applied to the well-known "Lemons Problem".
Keywords: C72; D4; D82; D86; 330; voting; decoy votes; adversary; electronic voting; attacks; lemons market